TERMINAL SOLID SOLUBILITY OF Gd IN Fe - Atiq, S; Rawlings, R D; West, DR E (Biological Sciences - PJSIR, 2002)
The constitutional data on Fe-Gd system do not include precise values of the extent of solid solubili ty of Gd in Fe. On the basis of investigations on the changes in oc1iron transition temperature (as a function of Gd contents) it has been established that Gd in concentrations up to 0.2 at % decreases th e tem perature of oc-y transition and its effect is therefore , as a stabilizer of y iron. Higher concentration of Gd in iron however , act as "bee" stabilizer by increasing the , oc-y iron transformation temperature. The solid solubility of Gd in oc-iron at the peritectoid temperature of 931°C is -1.0 at %.